(untitled) (Progressive Agriculture, 2013)
The present study was conducted for the detection of toxic effects of clostridial crude toxin in experimental rats. The crude toxin of Clostridium perfringens was prepared and the rats were injected intraperitoneally (IP) 0.5 ml, 1.0 ml and 2.0 ml of crude toxin. The rats were observed for 24 hrs. The crude toxin inoculated rats showed the dose dependent clinical signs; depression, rough hair coat, respiratory distress, diarrhea and rapid heart beats, whereas PBS inoculated rats did not show any clinical sings. Necropsy changes were variable however, highly dilated and distended whole intestine with blood stained semifluid contents and gas along with congestion in all the affected rats were found dose dependently. Liver, lung and kidney were congested, hemorrhagic and swollen. More or less hydrothorax was seen during the postmortem of all affected rats. The peritoneal fat was frequently congested in all affected rats. Histopathological changes in intestine (0.5 ml inoculated rats) involved congestion, slightly swollen goblet cells and hemorrhages. The most severe lesions comprised of profuse hemorrhages in the mucosa and submucosa with complete necrosis, desquamation and intense leukocytic infiltration in 2 ml inoculated rats. Affected liver (1 ml inoculated rats) exhibited engorgement of central veins, sinusoidal spaces with blood and fatty change. The hepatocytes revealed swelling, granulation and vacuolation of cell cytoplasm, extensive hemorrhage and congestion were seen in 2 ml toxin inoculated rats. Congestion and sometimes extravasation were observed in the subepicardial region of heart. The myocardium revealed mild degenerative changes in the form of granularity of myocardial fiber. In lungs there was congestion, hemorrhage and leukocytes infiltration in the interstitial spaces around the bronchioles in both 1 and 2 ml toxin inoculated rats. Affected kidneys of different doses of crude toxin showed hemorrhage, congestion and inflammatory cells dose dependently. From the above findings, it may be concluded that clostridial crude toxin induced clinical signs, gross and histopathological lesions dose dependently in experimental rats. DOI: http://dx.doi.org/10.3329/pa.v21i1-2.16753 Progress. Agric. 21(1 & 2): 65 - 72, 2010